2014
DOI: 10.1016/j.cpc.2014.06.006
|View full text |Cite
|
Sign up to set email alerts
|

A block-tridiagonal solver with two-level parallelization for finite element-spectral codes

Abstract: Abstract:Two--level parallelization is introduced to solve a massive block--tridiagonal matrix system. One--level is used for distributing blocks whose size is as large as the number of block rows due to the spectral basis, and the other level is used for parallelizing in the block row dimension. The purpose of the added parallelization dimension is to retard the saturation of the scaling due to communication overhead and inefficiencies in the single--level parallelization only distributing blocks. As a techni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…A cubic Hermite interpolating polynomial finite element (FE) discretization is used in the radial direction ψ to solve for the Fourier electric field coefficients E (m) (ψ) on a flux surface. TORLH solves for a single toroidal mode n φ , but multiple simulations at different toroidal mode numbers may be superimposed to reconstruct a 3-D field [40]. The use of a finite element basis in the radial direction, however, makes TORLH significantly faster (N fewer operations) and less memory intensive (N 2 less memory) than full-spectral solvers such as AORSA [41], but the use of a Fourier basis along each flux surface in TORLH allows inclusion of hot plasma effects in a fully self-consistent manner as the Fourier basis properly accounts for non-locality in the dielectric response on the flux surface.…”
Section: The Torlh Full-wave Solvermentioning
confidence: 99%
See 3 more Smart Citations
“…A cubic Hermite interpolating polynomial finite element (FE) discretization is used in the radial direction ψ to solve for the Fourier electric field coefficients E (m) (ψ) on a flux surface. TORLH solves for a single toroidal mode n φ , but multiple simulations at different toroidal mode numbers may be superimposed to reconstruct a 3-D field [40]. The use of a finite element basis in the radial direction, however, makes TORLH significantly faster (N fewer operations) and less memory intensive (N 2 less memory) than full-spectral solvers such as AORSA [41], but the use of a Fourier basis along each flux surface in TORLH allows inclusion of hot plasma effects in a fully self-consistent manner as the Fourier basis properly accounts for non-locality in the dielectric response on the flux surface.…”
Section: The Torlh Full-wave Solvermentioning
confidence: 99%
“…In TORLH, Helmholtz's equation ( 9) is put in Galerkin weak form and its dimension is reduced removing the radial field component E ψ (this reduction may be performed as we have ordered out the term ∝ σN 2 ⊥ corresponding to the pressure driven wave that occurs about the LH resonance and does not appear in LHCD scenarios [27]). Using discretization (5) a block tridiagonal matrix is produced which may be inverted to produce an electric field solution using a custom 3-D parallelized block-cyclic reduction solver [40].…”
Section: The Torlh Full-wave Solvermentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that a seemingly lesser algorithm can be much more efficient because it allows parallel processing [12][13][14][15] that is absolutely necessary for the use of the maximum computational power of modern processors, where thousands of tasks can be computed at the same time. The time when a personal computer's central processing unit (CPU) was able to compute only one thread at a time is over.…”
Section: Introductionmentioning
confidence: 99%